Begonia shunzhii (sect. Reichenheimia, Begoniaceae), a new species from Guizhou, China - Guo, Zhi-You; Bai, Xin-Xiang; Zhou, Xing-Xue; Chen, Zhi-Lin; Li, Yu-Hui; Tian, Dai-Ke (Phytotaxa, 2025)
Begonia shunzhii, a new species of Begonia sect. Reichenheimia from Guizhou Province of China is described and illustrated. It mostly resembles B. qingchengshanensis and B. puerensis in the same section but considerably differs from the latter two in some characteristics. A detailed morphological comparison of the three species is provided. According to the Guidelines for Using IUCN Red List Categories and Criteria, the conservation status of new species is assessed as Endangered (EN B1ab(i,ii,iii,iv,v)).